Floristic and ecological aspects of ferns and lycophytes of Seasonal Deciduous Forest remnants in Serra Gaúcha, Rio Grande do Sul, Brazil - Gonzatti, Felipe; Valduga, Eduardo; Wasum, Ronaldo Adelfo; Scur, Luciana (UFRGS, 2014)
In ten remnants of Deciduous Forest of the municipality of Santa Tereza, in Serra Gaúcha, afloristic/ecological survey of ferns and lycophytes was performed. The following ecological aspects were evaluated: preferred substrate, life form andpatterns of geographic distribution of species. We found 70 ferns and 4 lycophytes, belonging to 38 genera of 18 plant families. Pteridaceae was the richest family with 17 species and Polypodiaceae nine. The preferred substrate was the terrestrial, the predominant life forms were rosulate and reptant hemicryptophyte, followed by epiphytes. The predominant distribution patterns were South American (28 spp.), American (26spp.) and Circum-Antarctic (15 spp.). The results suggest a high diversity for this flora, characteristic of this vegetation type, with low registration epiphytism and endemic species. Em dez fragmentos de matas estacionais deciduais do município de Santa Tereza, na Serra Gaúcha, fez-se um levantamento florístico/ecológico das espécies de samambaias e licófitas. Foram avaliados os seguintes aspectos como caracteres ecológicos: substrato preferencial, forma de vida e padrões de distribuição geográfica das espécies. Foram encontradas 70 samambaias e quatro licófitas, pertencentes a 38 gêneros de 18 famílias botânicas. Pteridaceae foi a família com maior riqueza apresentando 17 espécies e Polypodiaceae com nove. O substrato preferencial evidenciado foi o terrícola, as formas de vida predominantes foram as hemicriptófitas rosuladas e reptantes, seguidas pelas epífitas. O padrão de distribuição predominante foi Sul-Americano (28 spp.), Americano (26 spp.) e Circum- Antártico (15 spp.). Os dados encontrados sugerem uma alta diversidade para esta flora, característica desta tipologia vegetacional, com baixo registro de epifitismo e espécies endêmicas.